(untitled) (Journal of the Bangladesh Agricultural University, 2018)
A taxonomic study on the weeds of the family Poaceae growing throughout the Bangladesh Agricultural University campus was carried out to determine species diversity of grasses in the campus. A total of 81 species under 46 genera and 2 subfamilies of the family Poaceae were collected and identified; their uses in various ailments were also recorded. Out of the three subfamilies, no weed from the subfamily Bambusoideae was found. Among the genera, Digitaria, Eragrostis, Brachiaria, Panicum, Echinochloa and Sporobolus were most dominant in context to number of species with a total of 29 species. While 28 genera were represented by single species each in BAU campus; of these 15 genera were in Bangladesh as well. Some of them are major and obnoxious weeds in different crop fields including staples rice and wheat. The flowering period will be helpful for the management of respective weed population. Many of these weed species have high economical, ethnomedicinal and other uses. The phenological study of these weed taxa will be helpful in managing weeds of the family Poaceae of this campus as well as the whole country without affecting the agro-ecosystem by keeping the weed population below a threshold level. J.Bangladesh Agril. Univ. 16(3): 372–379, December 2018